THE EFFECT OF CUSTOMER EXPERIENCE AND BRAND TRUST ON CUSTOMER LOYALTY AT PT SUMMIT OTO FINANCE PANGKALAN BUN - Sunarti (Branding: Jurnal Manajemen dan Bisnis, 2026)
In the landscape of automotive financing, delivering seamless credit, client interactions, and bolstering market reputation is no longer optional but essential for survival. For any enterprise, securing customer allegiance is an imperative, as it drives recurring business, fortifies long-term retention, and creates a competitive edge. Central to achieving such loyalty is the guarantee that every service touchpoint is perceived as dependable, uniform, and valuable, encouraging clients to repeatedly engage with the brand. This reality places an onus on PT Summit Oto Finance Pangkalan Bun Branch to evaluate the quality of its service delivery and the degree of confidence consumers place in its name. This investigation seeks to determine, through a quantitative methodology, the influence of experiential quality and brand credibility on the faithfulness of the branch’s clientele. Employing purposive sampling, the study gathered data from 90 participants via questionnaires, observation, interviews, and documentation, with analysis conducted using SPSS’s multiple regression. The outcomes reveal positive relationships: the calculated t-value for the experience-loyalty link (2.361) surpasses the critical threshold (1.987), and the t-value for brand trust (5.228) exceeds the same benchmark. Jointly, these predictors demonstrate a combined effect, evidenced by an F-value of 38.860 against a table value of 3.10. With an R² of 0.472, the model explains 47.2% of loyalty variance, leaving 52.8% attributable to elements. Indeed, these insights suggest that reinforcing brand trust through consistently positive encounters is pivotal for nurturing loyalty. Ultimately, the company must enhance overall service consistency, clear transparency, and clarity to sustain strong client relationships.